The Strategic Role of Islamic Kingdoms in Aceh in the 18th and 19th Centuries: The Case of Trade in Kuala Batee and Trumon - Inayatillah, Inayatillah; Rahmawati, Putri; Suryadi, S; Ramli, Ramli; Al Fairusy, Muhajir; Taran, Jovial Pally; Kurniawan, Ade (Journal of Al-Tamaddun, 2024)
Kuala Batee and Trumon kingdoms had an important role in the spice trade, especially pepper in the archipelago. Both kingdoms were fragments of the Susoh kingdom, all of which were special autonomous kingdoms under the Sultanate of Aceh Darussalam in the 18th century. A historical analysis approach knows several important findings. First, the Kuala Batee and Trumon kingdoms emerged as part of Aceh’s growing power on the South West Coast after it ceased to rule in Minangkabau in 1665. Secondly, these kingdoms were originally fragments of the Susoh kingdom. They were subject to the rule of the Sultan of Aceh before finally putting up a fight. Third, as Aceh’s control weakened, the Kuala Batee and Trumon kingdoms established trade relations with other regions, including Europeans and the United States, making them strategic powers in world trade.